EMOTIONAL ABUSE AMONG WORKING-CLASS WOMEN IN LAGOS STATE: IMPLICATION FOR COUNSELLING - SORIYAN, Tiwalade, O.; KAMALDEEN, Rahmat, T. (Journal of Professional Counselling, 2025)
This paper explores the incidence of emotional abuse among working-class women in Lagos State and its implications for counselling. The paper highlights the various forms of emotional abuse, including verbal abuse, isolation, and emotional blackmail, while also examining the root causes such as power imbalances, insecurity, cultural norms, and substance abuse. Emotional abuse in marriages is particularly prevalent, with long-term effects on the mental health, self-esteem, and well-being of victims. The paper further discusses the reasons women remain in abusive marriages, including fear, cultural pressures, economic dependence, and concerns about their children. It also emphasizes the role of counsellors in addressing emotional abuse by providing therapeutic support, promoting emotional healing, and empowering victims through techniques like Emotionally Focused Therapy (EFT), communication skills training, and conflict resolution strategies. The paper suggested that counsellors should engage in advocacy, continuous education, and collaborative efforts to raise awareness and improve support systems for victims.